The Effect of Aerobic Training on Weight Loss in Middle-Aged and Older Adults: Is It a Sufficient Form of Exercise? - Ptak, Anita; Szyc, Michał (Journal of Education, Health and Sport, 2025)
Introduction: Obesity is a serious health problem that affects a very large percentage of the population, including middle-aged and senior people. Overweight and obesity are risk factors for many diseases, including cardiovascular diseases and diabetes. Many papers have been produced investigating the effects of different types of training and diet on body fat levels in overweight and obese populations. One of the best studied forms of exercise is aerobic training. In this article, we will discuss the effects of aerobic training or its combination with resistance training on weight loss and fat burning in an elderly population, including those suffering from sarcopenic obesity. Aim of the study: To demonstrate the effects of aerobic training and the combination of aerobic training and resistance training on weight loss, body fat reduction and other relevant health parameters in a middle-aged and older population. Methods: A review of the literature available in PubMed and Google Scholar databases conducted using key words such as obesity, older adults, overweight, aerobic, resistance training. The review of available publications mainly focused on studies with the strongest scientific evidence such as randomised controlled trials and meta-analyses. Conclusion: Physical exercise is a crucial part of the fight against obesity. The implementation of training supports weight reduction and, at the same time, has a positive impact on fitness and physical performance. Aerobic training has a positive effect on weight loss, but the best results are obtained when aerobic training is accompanied by resistance training, as it has a positive effect on muscle strength and muscle tissue quality and has a positive effect on bone mineral density (BMD). However, it should be noted that significant fat reduction requires the implementation of a calorie deficit.